Análise econométrica da demanda de exportação de café brasileiro - Finageiv, Vicente; Brandt, Sérgio Alberto; Aad Neto, Alexandre; do Nascimento Santos, Heleno; Martins Rezende, Alberto; Ladeira, Heloisa Helena (Revista Ceres, 2025)
Coffee exported from Brasil to the world market, in the period from 1952 to 1973, grew at an average rate of 0.4% (1). In the same period, the average price increased at an annual average rate of 0.5%. Meanwhile, the Brazilian participation in the world market dropped from 52%, in 1952, to 31%, in 1973 (13).